Editorial: Towards a professionalisation of student affairs in Africa (Journal of Student Affairs in Africa, 2021)
The Journal of Student Affairs in Africa (JSAA) has been established as a platform for critically engaging with these developments by means of encouraging, supporting and disseminating high quality research and professional reflection from a diversity of national and institutional contexts. The JSAA is an independent, international, peer-reviewed, multi-disciplinary academic journal, established to serve the broad range of associations and professionals, institutions, centres and individual academics and researchers in the field. The JSAA publishes scholarly research and reflective-practitioner discussions about the theory and practice of student affairs in African higher education. It ultimately strives to become the foremost scholarly and professional journal dealing with the theory and practice of the student affairs domain in higher education on the African continent. As such it will be an indispensible resource for the executive leadership of universities and colleges dealing with student affairs, deans of students and other senior student affairs professionals, as well as institutional researchers, academics and students focused on the field of higher education studies and student affairs.
Keywords: high quality research; diversity; multi-disciplinary academic journal; theory and practice of student affairs; African higher education